Penerapan Tata Kelola Teknologi Informasi Dengan Menggunakan Framework Cobit 4.1 Pada RSUP. Cipto Mangunkusumo Jakarta - Efa Wahyuni; Noor Muhammad Adipati; Adelia Riana Dewi (Akuntansi research UGR, 2023)
Information Technology is a combination of computerization and telecommunication for procurement, processing, storage and dissemination of information. Utilization of Information Technology has become a necessity in efforts to increase the effectiveness and efficiency of business activities. Information technology in hospitals can be applied as a computer-based hospital service system (Computer-Based Library Systems) to manage administrative and service functions. The fundamental role of information technology in a company is needed to prevent problems that can occur within the company such as data loss, data leakage, inaccurate information available due to incorrect data making data integrity untenable, computer misuse and procurement of high-value information technology investments but not offset by an appropriate return on value. For this reason, it is necessary to have an information system audit control mechanism for the management of information technology This study raises cases at RSUP. Cipto Mangunkusumo which is currently in the stage of implementing Information Technology governance as a way to achieve business goals so that the investment that has been issued is comparable to the business goals to be achieved by the hospital. Based on the research that has been done, the results of the analysis of most of the process implementation of the COBIT 4.1 Framework in hospitals. Cipto Mangunkusumo is at this level of maturity throughout the IT process in the hospital. Cipto Mangunkusumo is on an average scale of 4, namely Manager, which means it is possible to monitor and measure adherence to procedures so that action can be easily taken if existing processes are not running effectively. Process improvements are carried out regularly and provide best practices.